Jesus Against the Forces of Death Reading Matthew Thiessen’s Reading of the Gospels’ Reading of Jesus’ War Against Ritual Impurity - Runesson, Anders 1968-; Thiessen, Matthew 1977- (2022)
Thiessen’s book is a systematic attempt at making obsolete an entire research paradigm, which has portrayed Jesus and the gospels as targeting for eradication the Jewish purity system itself, understood as an oppressive social mechanism with which the elite controlled the masses, rather than these texts describing a war against the impurity that this system defined and was meant to control. This essay engages this thesis.
Keywords: Rezension